Solusi Persamaan Dirac Untuk Potensial Manning Rosen Hyperbolik Plus Potensial Tensor Tipe Coulomb Pada Pseudospin Simetri Menggunakan Polynomial Romanovski - Kholida Ismatulloh; Yosi Nur Kholisho; Baiq Desi Dwi Arianti (Universitas Hamzanwadi, 2024)
The relativistic energy and wave function for the hyperbolic Manning Rosen potential with Coulomb-type tensor potential in the case of pseudospin symmetry are obtained from solving the Dirac equation using the Romanovski polynomial method. Using the appropriate wave function and variable substitution to reduce the second-order differential equation to a hypergeometric-type equation, the Dirac equation can be solved using Romanovski polynomials. The relativistic energy equation and weight function for Romanovski polynomials are produced by comparing the standard differential and hypergeometric type equations. Relativistic energy can be determined by employing numerical techniques and Matlab software to solve the relativistic energy equation. The weight function yields the relativistic wave function, which is then represented for the lower component of Dirac spin in the form of Romanovski polynomials